What Is Hell? How Daoism Challenges the Strong View - Bony Schachter (Religions)
This article argues that Daoism embodies a performative approach to hell. To make this argument, the first section summarizes the “strong view of hell”. The second section explores how the Daoist text Scripture of the Three Offices (Sanguan jing 三官經) describes hell. The third section examines how the Daoist priest Nie Shihao 聶士豪 (fl. 1691) interprets this description of hell. His commentary shows that Chinese rituals constitute a venue whereby social actors pursue ritual criticism and self-reflexivity.